2012
DOI: 10.1371/journal.pone.0051348
|View full text |Cite
|
Sign up to set email alerts
|

Light Accelerates Morphogenesis and Acquisition of Interlimb Stepping in Chick Embryos

Abstract: Chicks are bipedal precocious vertebrates that achieve adaptive locomotor skill within hours after hatching. Development of limb movement has been extensively studied in the chicken embryo, but few studies have focused on the preparations leading to precocious locomotor skill. Chicks typically hatch after 21 days of incubation, and recent studies provided evidence that the neural circuits for intralimb control of stepping are established between embryonic days (E) 18–20. It has also been shown that variations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 52 publications
2
22
0
Order By: Relevance
“…Left and right homologous muscles burst alternately, as observed during the stepping of left and right legs. Further, left-right alternation of leg muscle activity was more commonly observed in flexors than extensors 1 day prior to hatching and onset of walking (Sindhurakar & Bradley, 2012). These studies also observed that extensors frequently dropped out or failed to burst rhythmically during RLMs.…”
Section: Introductionmentioning
confidence: 51%
See 1 more Smart Citation
“…Left and right homologous muscles burst alternately, as observed during the stepping of left and right legs. Further, left-right alternation of leg muscle activity was more commonly observed in flexors than extensors 1 day prior to hatching and onset of walking (Sindhurakar & Bradley, 2012). These studies also observed that extensors frequently dropped out or failed to burst rhythmically during RLMs.…”
Section: Introductionmentioning
confidence: 51%
“…However, in many sequences, one muscle was consistently active, and the antagonist muscle failed to produce one or more bursts. EMG bursts were detected and analyzed based on previously established criteria (Bradley et al, 2008;Bradley, Ryu, & Yeseta, 2014;Ryu & Bradley, 2009;Sindhurakar & Bradley, 2012 five rhythmic bursts, and the right TA (r-TA) failed to produce bursts during three of the RLM cycles (asterisks). For example, in Figure 2B, the hip flexor (SA) produced 11 bursts (10 cycles), and its antagonist (CF) failed to produce bursts that met detection criteria in four cycles (noted by asterisks).…”
Section: General Features Of Rlm Emgmentioning
confidence: 99%
“…Though there were no differences in egg weight, body weight or toe length, tibia length varied positively with light exposure and was significantly shorter for chicks incubated in 24D compared to 24L. Further, differences in muscle activity and practice of locomotor-related leg movements in ovo (Sindhurakar & Bradley, 2012), might have contributed to differences in balance control at hatching. Both muscle fiber development and muscle activity are enhanced by light exposure and also contribute to bone maturation (Liu, Wang, & Chen, 2010; Hall & Herring, 1990).…”
Section: Discussionmentioning
confidence: 91%
“…Incubation conditions for this study were previously described (Sindhurakar & Bradley, 2010, 2012). In brief, incubators were configured for 1 of 3 light exposures that varied light intensity and exposure duration: 650-3000 lux, 12 hr daily (12L); 4000-7000 lux, 24 hr daily (24L); or ≤ 1 lux, 24 hr daily (24D).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation